IBM System Storage DS6000 Series Copy Services in Open Environments - Dufrasne, Bertrand; Castets, Gustavo; Baird, Stephen; Bauer, Werner; Brown, Denise; Jamsek, Jana; Kalabza, Wenzel; Klee, Peter; Oscheka, Markus; Thia, Ying; Tondini, Robert (IBM Redbooks, 2006)
This IBM Redbooks publication helps you install, tailor, and configure Copy Services in open systems environments on the IBM System Storage DS6000 storage server series. It should be read in conjunction with the IBM System Storage DS6000 Series: Architecture and Implementation, SG24-6781. This book gives you the details necessary to configure each of the Copy Services functions in an open systems environment. There is a companion book that supports the configuration of the Copy Services functions in a z/OS environment, IBM System Storage DS6000 Series: Copy Services with System z servers, SG24-6782. This book helps you design and create the storage map and install Copy Services in an open systems environment. This book helps you design and create a new Copy Services installation or to migrate from an existing installation, as well as addresses design functions and changes in terminology from other IBM Copy Services products. We include hints and tips to maximize the effective installation. It also includes a section on System i and an overview of the TotalStorage Productivity Center for Replication.
Online resource; Title from title page (viewed November 28, 2006)
Keywords: Data recovery (Computer science); Data recovery; Electronic data processing -- Backup processing alternatives; Storage area networks (Computer networks); Storage area networks; Récupération des données (Informatique); Sauvegarde (Informatique); Réseaux de stockage (Informatique); Electronic data processing; Backup processing alternatives